Study of waterproofing failures and proper installation method / Mohd Razif Romli - Romli, Mohd Razif (Faculty of Architecture, Planning and Surveying, 2009)
Waterproofing has become one of the important components in a building. It can be heard on news if there is a newly building, one of the problem arise must be related to toilet leakage. This is not due to lack of effective waterproofing systems and the products available in the market. To prevent damage and to avoid unnecessary repairs to building, groundwater, rainwater and surface water should be in control. As we know water has become the most destructive weathering element of concrete, brick walls, and the natural stone structures. Slowly, water will destruct buildings if the presence of it is not well monitored. Detailing of building transition from one building fagade component to the next should be improvised to avoid water infiltration. If water infiltration occurs, it also may lead to the mold growth and the related health issues of building occupants. Construction at sites often integrates different components to form a stable standing building. However, failure to put all these components together seems to cause weather and water intrusion problems. Failing to control installation and details linking various building facade components that for the building’s external skin creates miscellaneous problems related to the design and construction works.